KAJIAN TERHADAP TINGKAT PEMERATAAN PENDIDIKAN MENGGUNAKAN ANALISIS BIPLOT KLASIK DAN BIPLOT KEKAR - KUSUMAYANTI, NI LUH ARDILA; SUKARSA, I KOMANG GDE; OKA, TJOKORDA BAGUS; N. KENCANA, I PUTU EKA (E-Jurnal Matematika; Vol 4 No 2 (2015), 2015)
The aim of this research is to find the better from classical and robust biplot in determine dominant indicators of educational equity in Bali, NTB and NTT Provinces. This research based on secondary data obtain from Central Bureau of Statistics for year 2012/2013. Educational equity was portraited by Classical and Robust Biplot. The results of this research showed Robust Biplot is better method which goodness of fit is 90,64% meanwhile Classical Biplot as much as 83,62%. The Robust Biplot showed Students- Junior or Islamic Middle School Ratio and Students-Senior or Islamic High School were dominant indicators to educational equity in Bali,  NTB and NTT Provinces.
Keywords: educational equity; education indicators; classical biplot; robust biplot